Comparison of the static and dynamic balance between normal-hearing and hearing-impaired wrestlers - Coskun, B.; Unlu, G.; Golshaei, B.; Kocak, S.; Kirazci, S. (Montenegrin Journal of Sports Science and Medicine, 2019)
Balance is fundamental in sport, especially when there is an opponent. Although balance can be improved with practice, it is highly affected by nervous system disorders, particularly by vestibular disorders and visual impairment. The purpose of this study was to compare static and dynamic balance between normal and hearing-impaired wrestlers. The participants were 52 young male hearing-impaired wrestlers (n=29, age=18.76±3.54) and normal-hearing athletes (n=23, age=19.09±2.76) competing at the national level. The static and dynamic balance were measured using the stork test on one foot and the Y-balance test (in anterior, posteromedial & posterolateral directions). MANOVA indicated significant differences between groups (Wilks` L=.284, F12,39=8.21, p2=.72). Differences were detected in how long the participant had been active in the sport F(year) (F1,50=145.95, p2=.75) and right leg static balance (F1,50=73.63, p2=.60). As for the Y balance test, there was also a significant difference in the anterior direction for the right leg (F1,50=4880.66, p2=.99) and left leg (F1,50=3563.87, p2=.99). Hearing-impaired wrestlers performed better balance abilities in the dynamic balance test of right and left legs in the anterior direction. In contrast, the amount of time active in the sport and the static balance of the right leg were found better in normal-hearing wrestlers. Being better than normal wrestlers only in the anterior direction of the dynamic balance might be due to the differences related to the directions of the test. Future studies are recommended for investigating the reasons for this difference.